Extensively Drug-resistant Salmonella typhi Meningitis in a 16-year-old Male - Khurshid, Noman (Cureus, 2019)
Meningitis caused by Salmonella enteritidis is an uncommon infection, linked with great mortality and neurological problems, which makes prompt diagnosis and treatment very crucial. Patients of bacterial meningitis present with common symptoms such as headache, fever, altered level of consciousness, and neck rigidity. A positive gram stain or culture of cerebrospinal fluid (CSF) leads to its diagnosis. In this report, we present a case of a 16-year-old male with extensively drug-resistant (XDR) Salmonella typhi meningitis, which was not responsive to initial medical intervention. He was treated with meropenem, imipenem, azithromycin, and metronidazole. Immediate tracheostomy and intubation were performed in the surgical intensive care unit (ICU), as the patient had developed stridor, shortness of breath, tachypnea, tachycardia, and had severely decreased O(2) saturation of 60%. As far as treatment is concerned, third-generation cephalosporins are considered the treatment of choice. In addition, the use of fluoroquinolones and carbapenems, mainly meropenem, has also been described as a therapeutic alternative.